2021
DOI: 10.3389/fpubh.2021.631212
|View full text |Cite
|
Sign up to set email alerts
|

Ex-Drug Users' and Health Professionals' Perspectives About School-Based Drug Use Prevention Programs: A Qualitative Study

Abstract: Adolescents have become a prime target for drug dealers in various countries around the world, including in Indonesia. To reduce the high number of drug users amongst adolescents, effective drug prevention programs should be developed and implemented. The present study aimed to identify effective school-based drug prevention programs for adolescents from the perspectives of former drug users and health professionals. This qualitative research used Focus Group Discussions (FGDs) to collect the data. The study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Traditionally, substance abuse prevention programs like the ones listed have focused primarily on psychoeducation and raising awareness; however, an emerging body of literature has demonstrated that substance use recovery and prevention is also associated with psychosocial and well-being factors such as hope, meaning in life, emotional intelligence, and social connections (Gutierrez, 2019; Gutierrez et al, 2020; Merchán-Clavellino et al, 2020; Wyrick et al, 2001). A recent article exploring the success of drug prevention programs reported findings that supported the need for coordination and cooperation among stakeholders such as peer groups, teachers, and parents (Tahlil & Aiyub, 2021). Ex-drug user participants reported that cooperation among external stakeholders, such as the Department of Education, schools, and community health agencies, was important (Tahlil & Aiyub, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, substance abuse prevention programs like the ones listed have focused primarily on psychoeducation and raising awareness; however, an emerging body of literature has demonstrated that substance use recovery and prevention is also associated with psychosocial and well-being factors such as hope, meaning in life, emotional intelligence, and social connections (Gutierrez, 2019; Gutierrez et al, 2020; Merchán-Clavellino et al, 2020; Wyrick et al, 2001). A recent article exploring the success of drug prevention programs reported findings that supported the need for coordination and cooperation among stakeholders such as peer groups, teachers, and parents (Tahlil & Aiyub, 2021). Ex-drug user participants reported that cooperation among external stakeholders, such as the Department of Education, schools, and community health agencies, was important (Tahlil & Aiyub, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A recent article exploring the success of drug prevention programs reported findings that supported the need for coordination and cooperation among stakeholders such as peer groups, teachers, and parents (Tahlil & Aiyub, 2021). Ex-drug user participants reported that cooperation among external stakeholders, such as the Department of Education, schools, and community health agencies, was important (Tahlil & Aiyub, 2021). Efficacious prevention programs also seek to address cultural values, developmental needs, and attitudes of the group (Edalati & Conrod, 2018).…”
Section: Introductionmentioning
confidence: 99%